Working-Class Literature(s) Volume II - Lennon, John; Nilsson, Magnus (Stockholm University Press, 2020)
The aim of this collection is to contribute to the forging of a more robust, politically useful, and theoretically elaborate understanding of working-class literature(s).These essays map a substantial terrain: the history of working-class literature(s) in Argentina, Denmark, Germany, Japan, Singapore, South Africa and Ireland. Together with the essays in a previous volume – which cover Russia/The Soviet Union, The USA, Finland, Sweden, The UK, and Mexico – they give a complex picture of working-class literature(s) from an international perspective, without losing sight of national specificities.By capturing a wide range of definitions and literatures, the two volumes give a broad and rich picture of the many-facetted phenomenon of working-class literature(s), disrupt narrow understandings of the concept and phenomenon, as well as identify and discuss some of the most important theoretical and historical questions brought to the fore by the study of this literature.If read as stand-alone chapters, each contribution gives an overview of the history and research of a particular nation’s working-class literature. If read as a whole (which we hope you do), they contribute toward a more complex understanding of the global phenomenon of working-class literature(s).
Keywords: International literature; Politics; Socialism; Working-class literature